2020
DOI: 10.1038/s41699-020-00168-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of high-quality monolayer tungsten disulfide with chlorophylls and its application for enhancing bone regeneration

Abstract: Due to the population explosion of the 21st century, nearly one billion people are over 64 years of age and bone fracture is one of the most frequent problems facing both sexes because of osteoporosis. However, difficulty in enhancing bone regeneration to repair bone fracture poses challenges and thus, a two-dimensional monolayer material (i.e. tungsten disulfide (WS2)) could be one of the candidates offering a possible solution to the problem. Here, we prepare high-quality monolayer WS2 thin sheets in a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 63 publications
2
10
0
Order By: Relevance
“…Group 8 showed complete resistance to tumor growth, and the tumor almost disappeared after 12 days due to combined PTT & PDT. These results demonstrated the good in vivo anticancer ability of Chl/V 2 C NSs [30].…”
Section: In Vivo Anticancer Performance Of Chl/v 2 C Nssmentioning
confidence: 56%
“…Group 8 showed complete resistance to tumor growth, and the tumor almost disappeared after 12 days due to combined PTT & PDT. These results demonstrated the good in vivo anticancer ability of Chl/V 2 C NSs [30].…”
Section: In Vivo Anticancer Performance Of Chl/v 2 C Nssmentioning
confidence: 56%
“…coli and Gram-positive B. subtilis bacteria, which were in agreement with the previous report owing to alterations in the bacterial cell wall structure. The typical photograph of the recultivation experiment also confirmed that the V 2 C NSs+ laser treatment showed the strongest inhibition of both bacteria compared with V 2 C NSs, laser, and the control (Figure E). , The comprehensive statistical analysis of Figures E and E are demonstrated in Figure S5.…”
Section: Results and Discussionsupporting
confidence: 89%
“…At the end of 7 days of immersion, the release of 1.2 mM, 0.95 mM, and 0.65 mM of Si ions was noted from G5, G2, and G0, respectively. In fact, the MSCS scaffold is already a material that can regulate cell behaviors, mainly because it spontaneously releases Si ions to promote the proliferation and differentiation of various primary cells [ 38 , 39 ]. Moreover, Si ions were known to enhance collagen secretion and angiogenesis in the mid-stages of bone regeneration [ 17 ].…”
Section: Resultsmentioning
confidence: 99%